PENGARUH STATIC CYCLE TERHADAP PENINGKATAN ENDURANCE DAN KEKUATAN OTOT QUADRICEPS PADA PASIEN KANKER TESTIS - Ratu Rania,; Komala Sari, Dwi Rosella (Jurnal Kesehatan, 2024)
Testicular cancer is the most common type of cancer in young adult men. Testicular cancer is a malignant disease that originates from testicular cells. The highest incidence rates of testicular cancer are in Europe, America, and Australia, while the lowest rates are in Asia and Africa. The aim of the research was to determine the effect of the static cycle on endurance and quadriceps muscle strength in cases of testicular cancer. The research was carried out as a single case study with a pre and post test research design, namely comparing assessments before and after being given physiotherapy intervention. The research was carried out by providing physiotherapy interventions and a home program which will be evaluated every week for 1 month using the intervention and 1 month without intervention. The results showed that there were increases and decreases in the first to eighth evaluations. The decrease in evaluation occurred because the patient was undergoing chemotherapy. Chemotherapy can cause reductions in muscle mass and strength and tends to cause unfavorable changes. However, for 1 month at home without intervention, the patient was given a home program in the form of wall squat exercises, straight leg raises exercise, step ups exercise and breathing exercise, there was an increase in muscle strength and endurance.